Morphological characteristics and systematic position of Allium guanxianense, an endemic species from Sichuan, China - Yuan Wang; Deng-Feng Xie; Bo-Ni Song; Lian Chen; Yu-Lin Xiao; Xing-Jin He (Journal of Asia-Pacific Biodiversity)
The research examined the chloroplast genome structure and evolutionary relationships of Allium guanxianense. The cp genome spans 152,480 bp and comprises a large single copy region (82,305 bp, 53.98% length ratio), a small single copy region (18,353 bp, 12.04%), and two inverted repeat sequences (25,911 bp, 16.99%). A total of 132 genes were identified within the cp genome of A. guanxianense, including 86 protein-coding genes (PCGs), 38 tRNAs, and 8 rRNAs. Its cp genome structure is basically consistent with other species of the sect. Bromatorrhiza, with the only difference being the distributions of ndhF and rpl22 at the IR region. The codon usage bias analysis for PCGs revealed that mutation pressure drives the preference for codon usage in Allium species. Phylogenetic analysis of 35 Allium species showed that the genus can be divided into three major lineages, with A. guanxianense positioned at the top of the sect. Bromatorrhiza in first lineage, forming a well-supported sister clade with A. omeiense. Our study presents, for the first time, the morphological characteristics and chloroplast genome features of A. guanxianense, and analyzes its relationship with closely related species. This is of significant importance for the classification, phylogeny, and conservation of this narrowly distributed endemic species.